Somatosensory profiles of patients with chronic myogenic temporomandibular disorders in relation to their painDETECT score - C. Welte-Jzyk; D. B. Pfau; A. Hartmann; M. Daubländer (BMC, 2018)
Abstract Background The purpose of this study was to characterize patients with chronic temporomandibular disorders (TMD) in terms of existing hyperalgesia against cold, heat and pressure. Methods The extent of hyperalgesia for pressure and thermal sensation in TMD patients was determined by the use of the painDETECT questionnaire ("Is cold or heat in this area occasionally painful?" "Does slight pressure in this area, e.g., with a finger, trigger pain?") and experimental somatosensory testing against thermal and pressure stimuli (Quantitative Sensory Testing; QST). In addition, we explored psychological comorbidity among the chronic TMD patients (hospital anxiety and depression scale, HADS-D and coping strategies questionnaire, CSQ). Results Nineteen patients with chronic TMD and 38 healthy subjects participated in the study. N = 12 patients had a painDETECT score ≤ 12, n = 3 patients had a painDETECT score of 13-18 and n = 4 patients had a painDETECT score ≥ 19. TMD patients with painDETECT scores ≥19 had moderately, strong or very strong enhancement of thermal and pressure pain perception, whereas patients with painDETECT scores 13-18 and ≤ 12 responded these questions with "never", "hardly noticed" or "slightly painful" (p < 0.05-0.01). With increasing painDETECT scores we found increased hyperalgesia for pressure (p < 0.01) and thermal stimuli (p < 0.05) in QST. The patients with a painDETECT score ≥ 19 showed increased signs of anxiety (p < 0.05), depression (p < 0.01), praying and hoping (p < 0.05). Conclusion The present study has shown that the PainDETECT questionnaire can be a helpful additional diagnostic tool. Together with QST, the PainDETECT questionnaire detected hyperalgesia for pressure and thermal sensation. Therefore the PainDETECT questionnaire is helpful to decide which TMD patients should undergo QST.